Analisis Tingkat Pengetahuan Dan Kesiapsiagaan Masyarakat Terhadap Pertolongan Pertama Pada Kasus Hipoglikemia: Analysis of Community Knowledge and Preparedness Levels Regarding First Aid for Hypoglycemia Cases - Ariani, Sri Purwanti Ariani; Ernawati, Ernawati; Rapika, Rapika (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Hypoglycemia is an emergency condition that can occur suddenly, especially in patients with diabetes mellitus, and may lead to loss of consciousness, seizures, and even death if not treated promptly. Delays in providing first aid are often caused by low levels of community knowledge and preparedness in recognizing the signs and symptoms of hypoglycemia. Therefore, this study aims to analyze the level of knowledge and preparedness of the community regarding first aid for hypoglycemia cases in Basirih Village. This study used a descriptive analytic design with a cross-sectional approach. The study sample consisted of adults in Basirih Village selected using a purposive sampling technique. The variables studied included knowledge level as the independent variable and community preparedness for first aid in hypoglycemia cases as the dependent variable. Data were collected using a structured questionnaire that had been tested for validity and reliability, and then analyzed using univariate and bivariate analysis. The results showed that most respondents had a moderate level of knowledge, while community preparedness for providing first aid in hypoglycemia cases was still in the low category. Bivariate analysis indicated a relationship between knowledge level and community preparedness, where respondents with higher knowledge tended to have better preparedness in providing first aid for hypoglycemia cases. In conclusion, there is a relationship between knowledge level and community preparedness in providing first aid for hypoglycemia cases. Therefore, continuous health education efforts through community-based health promotion programs are needed to improve knowledge and preparedness, enabling the community to respond quickly and appropriately to hypoglycemia emergencies.